El impacto de las pruebas internacionales en la medición de la calidad educativa en américa latina (2023)
This article is a reflection on international standardized tests and their relationship with the international organizations that regulate this system, their measurement and impact with educational institutions. It is an opportunity to take a look and see the role played by bodies such as the Organization for Economic Cooperation and Development (OECD), UNESCO, among others, in establishing international policies that impact the development of teaching-learning processes. Standardized tests are part of the accumulation of external instruments that have been created to measure educational quality. On many occasions it is thought that the low level of results in international tests is the teachers’ fault, however, it is verified that they can contain a minimal part in all these realities. Finally, it is concluded that standardized tests are designed to generalize the cognitive ability of students at different levels. This test assumes that each step must respond to the corresponding educational level; forgetting the vulnerable sociocultural situation experienced by a significant percentage of students.